Key business concepts : a concise guide - Karlöf, Bengt, 1939-; Gilderson, Allan J. (London ; New York : Routledge, 1993)
This book is about: Introduction; Glossary; and Models of Business concepts.
Keywords: Business; Dictionaries; Business -- Dictionaries